2020
DOI: 10.1097/nne.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

Restrictions on Nursing Students' Electronic Health Information Access

Abstract: Background Restrictions on students' use of electronic health information have been anecdotally reported as a threat to clinical learning, development of informatics competency, and adherence to personal health information privacy laws. However, evidence on which informatics education and policy strategies can be designed is lacking. Purpose This study describes the scope of nursing students' access to and use of electronic health information systems as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
4
13
0
1
Order By: Relevance
“…Nagle et al [ 5 ] identified that teaching students about the use of EHRs is challenging in practice settings because there are few opportunities for students to access or use fully functional EHR systems in health care facilities. These findings are congruent with our findings and those in the general literature [ 11 , 34 ]. Nagle et al [ 5 ] also highlighted the need for an affordable EHR sandbox that could be used in simulation laboratories to teach students how to integrate these tools as they learn other clinical skills.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Nagle et al [ 5 ] identified that teaching students about the use of EHRs is challenging in practice settings because there are few opportunities for students to access or use fully functional EHR systems in health care facilities. These findings are congruent with our findings and those in the general literature [ 11 , 34 ]. Nagle et al [ 5 ] also highlighted the need for an affordable EHR sandbox that could be used in simulation laboratories to teach students how to integrate these tools as they learn other clinical skills.…”
Section: Discussionsupporting
confidence: 94%
“…They indicated that opportunities for electronic documentation will not only strengthen their communication skills but also enhance their critical thinking skills and their understanding of informatics concepts. It could ease their transition to using advanced technology in the work setting, which is congruent with findings from previous research [ 11 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the lack of access to patient information through the electronic health record was perceived as the second greatest barrier to student learning by faculty, this can occur in the clinic setting as well. Access to the electronic health record for health professions' students has been cited as a barrier to learning, but due to the difficulty in onboarding students to obtain access as well as privacy issues, this remains a challenge (ACS, 2018; Hansbrough et al, 2020).…”
Section: Discussionmentioning
confidence: 99%